DESCRIPTION OF MOTHER BEHAVIOR IN ANEMIA PREVENTION EFFORTS IN BASIC SCHOOL CHILDREN IN CINDEREJO ELEMENTARY SCHOOL, CITY OF SURAKARTA. - pitoyo mumpuni; Bagoes Widjanarko; Ratih Indraswari (Jurnal Kesehatan Masyarakat, 2019)
Anemia is a major health problem that affects almost half of children in developing countries, including in Indonesia. Indonesian people as much as 21.7% reduce anemia.The prevalence of anemia in the age group of 5-14 years is 26.4%, whereas in the age group of 15-24 years it is 18.4%. 4 Factors in nutritional status influence the occurrence of anemia, so food consumption as a nutrient intake for young women needs to get the most attention. The role of parents is very important in determining family health.This study aims to describe and provide an overview of parental behavior in an effort to prevent anemia in elementary school children in cinderejo,Surakarta city.The method used in this research is descriptive with crossectional research design. The population in this study were parents of students from grade 1 to grade 6 in Cinderejo Elementary School as many as 142 children. This study used total sampling. The results showed that respondents had good knowledge of 77.5%, the good attitude at 100%, and good practise about 88,7%. Respondents got information from community health centers officers at 80.99%, counseling was the most widely used media (87.3%), and respondents who received information from schools through counseling as much as 67.6%.Needed for a program that can overcome the problem of anemia in elementary school children.